2012
DOI: 10.1109/tuffc.2012.2347
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic scanner for in vivo measurement of cancellous bone properties from backscattered data

Abstract: A dedicated ultrasonic scanner for acquiring RF echoes backscattered from the trabecular bone was developed. The design of device is based on the goal of minimizing of custom electronics and computations executed solely on the main computer processor and the graphics card. The electronic encoder-digitizer module executing all of the transmission and reception functions is based on a single low-cost field programmable gate array (FPGA). The scanner is equipped with a mechanical sector-scan probe with a concave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, precise differentiation of the echo of the pin inserted in bone tissue remains difficult because of the complex echographic response of the trabecular structure (Litniewski et al 2012). Therefore, the signal corresponding to the ultrasonic response of bone tissue located between the pin and the transducer is removed by considering the echo of the pin only given by…”
Section: Determination Of the Ultrasonic Parametersmentioning
confidence: 99%
“…However, precise differentiation of the echo of the pin inserted in bone tissue remains difficult because of the complex echographic response of the trabecular structure (Litniewski et al 2012). Therefore, the signal corresponding to the ultrasonic response of bone tissue located between the pin and the transducer is removed by considering the echo of the pin only given by…”
Section: Determination Of the Ultrasonic Parametersmentioning
confidence: 99%
“…Although most research has indicated that backscatter is positively related to cancellous bone status (i.e., BMD, BV/TV and ultimate strength) (Karjalainen et al 2009(Karjalainen et al , 2012Litniewski et al 2012;Moayyeri et al 2012;Riekkinen et al 2007;Wear et al 2012;Zhang et al 2013), some studies have reported a negative correlation (Hoffmeister 2011a;Hoffmeister et al 2000Hoffmeister et al , 2006Hoffmeister et al , 2008Hoffmeister et al , 2011. This contradiction has confused researchers and has obstructed clinical applications of ultrasonic backscatter for cancellous bone assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of backscatter studies have been performed at the hip and spine of human volunteers. [5][6][7][8] Backscatter occurs as an ultrasonic wave interacts with the trabecular microstructure of cancellous bone. The conventional approach is to measure the backscatter coefficient or the frequency averaged backscatter coefficient from cancellous bone.…”
Section: Introductionmentioning
confidence: 99%